Research on the Equal Probability Grouping Method for Automatic Fitting of Deep Groove Ball Bearings - Peiqi Yang; Haoyi Wang; Xuejun Li; Linli Jiang (Machines)
At present, the fitting process of deep groove ball bearings has the problems of low manual production efficiency and poor performance of fitted bearings. For the automatic bearing fitting production line, there are some problems, such as a low success rate of fitting and easy interruption of the production process. In this article, two grouping methods, the equidistant grouping method and the equal probability grouping method, are proposed. We establish a dimensional deviation distribution model by measuring the dimensional deviation of deep groove ball bearing components. Using the bearing component dimensional deviation distribution model, we carry out the equidistant grouping method and the equal probability grouping method to fit the bearing component. And the influence of the traditional bearing fitting method and the two grouping methods on the success rate of deep groove ball bearing fitting is compared and analyzed. This research found that the traditional bearing fitting method is easy to fall into local optimization, and too many unmatched components which have a larger dimensional deviation lead to the interruption of the fitting process. The success rate of the traditional fitting method is lower than grouping methods. For the two grouping methods, the equal probability grouping method can ensure that the probability of each group of components entering the automatic production line is the same. Compared with the equidistant grouping method, it is easier to make it possible to fit the bearing component. The equal probability grouping method is recommended.